The use Of pictogram in electronic appliance - Tiurmaya; Fitriany; Fauziah Nur; Suryani Nadeak (ARKA INSTITUTE, 2022)
The research aim is to describe the types of pictogram use and the reason why pictograms are used. The type of this research is descriptive qualitative. There are two sources of data first, five of manual book, such as: mobile phone, laptop, rice cooker, microwave, and washing machine. Second, data transcription of interview. This research focused on types of pictogram use and the reason why pictograms are use. The data were obtained by documentation and the data were analyzed stating by collect the data, the data divided to types of the pictogram use and analysis the reason of the pictogram depend on the interview. In the end analyses the use of pictogram by the manual of electronic appliance also the reason of used it depend on davies theory. The result of the research is From the data analysis found 57 pictograms use in five electronic manual books which are: Oppo Reno6 mobile phone, Panasonic rice cooker, Panasonic microwave, Asus laptop, LG washing machine. Were 27 of the pictograms are representational, 21 arearbitrary symbol and 9 are abstract symbol. Moreover according to theinterview pictogram is more easy to understand than word by the user of theelectronic.